(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Green hydrogen is becoming a key element in the global transition to sustainable and low-carbon energy systems. The article analyzes international trends in the development of hydrogen energy with an emphasis on the leadership of Germany and the real pilot project RefLau (Referenzkraftwerk Lausitz) - a reference hydrogen power plant implemented in the coal region of Lausitz (Brandenburg) as part of the decarbonization strategy. RefLau is a model for integrated green hydrogen production using renewable energy sources, electrolysis, storage and reuse of by-products. It also considers the strategy of Kazakhstan, which assumes a gradual transition from «blue» to «green» hydrogen, as a realistic path for countries with developed infrastructure and fuel resources. Particular attention is paid to Kyrgyzstan, which has significant hydropower potential.